Fluorescence imaging of beta cell primary cilia - Li, Zipeng A.; Cho, Jung Hoon; Woodhams, Louis G.; Hughes, Jing W. (Frontiers in Endocrinology, 2022)
Primary cilia are slender cell-surface organelles that project into the intercellular space. In pancreatic beta cells, primary cilia coordinate a variety of cell responses including GPCR signaling, calcium influx, and insulin secretion, along with likely many underappreciated roles in islet development and differentiation. To study cilia function in islet biology, direct visualization of primary cilia by microscopic methods is often a necessary first step. Ciliary abundance, distribution, and morphology are heterogeneous among islet cells and are best visualized by fluorescence microscopy, the tools for which are readily accessible to most researchers. Here we present a collection of fluorescence imaging methods that we have adopted and optimized for the observation of primary cilia in mouse and human islets. These include conventional confocal microscopy using fixed islets and pancreas sections, live-cell imaging with cilia-targeted biosensors and probes, cilia motion recordings, and quantitative analysis of primary cilia waveform in the ex vivo environment. We discuss practical considerations and limitations of our approaches as well as new tools on the horizon to facilitate the observation of primary cilia in pancreatic islets.